(untitled) (Research, Society and Development, 2021)
The purpose of this article is to address some characteristics that make up the concept of green marketing and its benefits used within corporations, as a way to generate targeted communication to a certain audience, to monetize their products/services and its importance as a basis for success of companies in the market, as a way of being presented as a competitive differential. In addition to the positive aspects in public opinion, this approach provides opportunities for strengthening the brand with consumers who prefer products that preserve the environment and generate long-term sustainability.